Performance Evaluation and Capacity Assesment of a CEPT for Metal Platting Industries - Singh, Vikas (My University, 2007)
vvA small-scale industrial unit (SSI) is defined as any industry whose plant and machinery are valued at less that 1 crore (Government of India is planning to increase this to 5 crores) [38]. SSI occupies an important place in Indian economy for their contribution to industrial production, exports and employment. Government policies have been biased toward SSI, even though small industries are highly polluting. SSIs contribute 40% of the total industrial output of the country. But generate over 44% of the hazardous wastes while contribution by the large-scale industry is 13% [43]. Quantity of waste generated by individual SSIs may not be large, but combined effect of operation of a large number of SSI units on the environment can be high, especially when they are clustered in certain locations closer to residential or commercial centers [45, 46]. Effluents generated by SSIs need treatment prior to disposal in order to comply with the prescribed effluent standards. SSIs face many difficulties to treat their wastes by themselves. Being small, installation and use of on-site effluent treatment facilities would not be efficient, in both environmental and economic terms. Further, SSIs may not have enough budget for the creation and effective use of the facilities. Availability of space to install the facilities may be a problem for many SSIs. Most SSIs can not have trained and dedicated manpower for effectively operating and using their facilities [21]. Common facilities and common effluent treatment plant (CETP) is widely believed as solution to the effluents problem for clusters of SSIs. World Bank under its "Pollution Prevention Programme" is promoting CETPs as a viable solution to control industrial pollution[52]. Further, in many cases, the courts have given the ruling to abate the pollution problems of SSIs through using the CETP concept [23]. Many CETPs have been installed and operated all over the country for tackling the water pollution problems arising from the clusters of SSIs.
Keywords: performance evaluation; wastewater sampling; capacity assesment